Patient and provider perspectives on uptake of a shared decision making intervention for asthma in primary care practices. (4th May 2019) - Welch, Madelyn; Ludden, Thomas; Mottus, Kathleen; Bray, Paul; Hendrickson, Lori; Rees, Jennifer; Halladay, Jacqueline; Tapp, Hazel
ABSTRACT: Objective: Poor outcomes and health disparities related to asthma result in part from difficulty disseminating new evidence such as shared decision making (SDM) into clinical practice. As part of a three-arm cluster randomized dissemination study, evaluation of the impact of different dissemination methods was studied. Here we evaluate themes from patient and provider focus groups to assess the impact of a facilitated, traditional dissemination approach, or no intervention, on patient and provider perspectives of asthma care. Methods: Using semi-structured questions, twenty-four pre- and post-intervention focus groups with patients and providers took place across primary care practices. Discussions were held in all three arms both before and after the time of intervention rollout. Audio recordings were transcribed and analyzed for themes. Results: Across all sites patients and providers discussed themes of communication, asthma self-management, barriers, education, and patient awareness. After the intervention, compared to traditional sites, facilitated practices were more likely to discuss themes related to SDM, such as patient-centered communication, patient-provider negotiation on treatment plan, planning, goal-setting, and solutions to barriers. Conclusions: Emergent themes allowed for further understanding of how the SDM implementation was perceived at the patient and provider level. The facilitated implementation was associated with higher adoption of the SDM intervention. These themes and supporting quotes add to knowledge of best practices associated with implementing an evidence-based SDM intervention for asthma into primary care and will inform researchers, practices, and providers as they work to improve adoption of evidence-based interventions into practice.